Технічні рішення щодо сушіння пташиного посліду - Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Skliar, Oleksandr; Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila; Григоренко, Сергій Михайлович; Григоренко, Сергей Михайлович; Hryhorenko, Serhii (ТДАТУ, 2020)
UK: В статті розглянуто існуюче обладнання для сушіння пташиного посліду. Доведено, що термічні способи переробки мають значні переваги перед іншими способами. Наведено, що технологічні прийоми переробки посліду повинні забезпечувати значне скорочення його об’ємів та отримання екологічно безпечного готового продукту. Найбільшого поширення набули установки для сушіння посліду тунельного типу з конвективним способом підведення теплоти. Проаналізовані варіанти установок для вакуумного сушіння, яке є новим способом для утилізації рідкого посліду. До переваг можна віднести: екологічну безпеку, високу якість одержуваного органічного добрива. Обґрунтовано, що незважаючи на ряд переваг, витрати на отримання сухого посліду при цьому виявляються досить високими, що стримує промислове застосування даного способу. Запропоновано пристрій для сушіння пташиного посліду, в якому пропонується ряд технічних рішень, що дозволять знизити питому енергоємність процесу сушіння посліду і поліпшити якість готового продукту. RU: В статье рассмотрено существующее оборудование для сушки птичьего помета. Доказано, что термические способы переработки имеют значительные преимущества перед другими способами. Показано, что технологические приемы переработки помета должны обеспечивать значительное сокращение его объемов и получения экологически безопасного готового продукта. Наибольшее распространение получили установки для сушки помета туннельного типа с конвективным способом подвода теплоты. Проанализированы варианты установок для вакуумной сушки, которая является новым способом для утилизации жидкого помета. К преимуществам можно отнести: экологическую безопасность, высокое качество получаемого органического удобрения. Обосновано, что несмотря на ряд преимуществ, затраты на получение сухого помета при этом оказываются достаточно высокими, что сдерживает промышленное применение данного способа. Предложено устройство для сушки птичьего помета, в котором предлагается ряд технических решений, которые позволят снизить удельную энергоемкость процесса сушки помета и улучшить качество готового продукта. EN: The article discusses the existing equipment for drying poultry manure. It has been proven that thermal processing methods have significant advantages over other methods. It is shown that technological methods for processing manure should provide a significant reduction in its volume and obtain an ecologically safe finished product. The most widespread are installations for drying manure of a tunnel type with a convective method of supplying heat. Multi-stage, which is used in practice for drying lines, leads to significant capital investments at the stage of formation of dehydration sections. In addition, the processes of evaporation and spraying, as a rule, are carried out at temperatures from 90 to 150 °C, which is unacceptable for substances such as vitamins, sugar, some protein compounds, amino acids and the like. It is desirable to process such substances in the temperature range from 40 to 90 °C. This temperature range can be provided only when the process is carried out under vacuum conditions. Variants of installations for vacuum drying, which is a new method for liquid manure disposal, have been analyzed. The advantages include: environmental safety, high quality of the resulting organic fertilizer. It has been substantiated that, despite a number of advantages, the costs of obtaining dry manure in this case are quite high, which hinders the industrial application of this method. A device for drying poultry manure is proposed, in which the installation of a transporting body in the gap between the casing and the perforated cylinder will allow achieving a constant temperature field as a result of a relatively small gap between the casing and the perforated cylinder, will also improve the quality of the finished product and reduce the specific energy consumption of the manure drying process.
Технические решения по сушке птичьего помета
Technical solutions for bird drying follow
Keywords: сушіння; пташиний послід; вакуум; органічне добриво; сушарка; енергоємність; сушка; птичий помет; вакуум; органическое удобрение; сушилка; энергоемкость; drying; bird droppings; vacuum; organic fertilizer; dryer; energy intensity